4(x-4)+3(x-4)=3

Simple and best practice solution for 4(x-4)+3(x-4)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-4)+3(x-4)=3 equation:



4(x-4)+3(x-4)=3
We move all terms to the left:
4(x-4)+3(x-4)-(3)=0
We multiply parentheses
4x+3x-16-12-3=0
We add all the numbers together, and all the variables
7x-31=0
We move all terms containing x to the left, all other terms to the right
7x=31
x=31/7
x=4+3/7

See similar equations:

| 9k-4k-5=10 | | 22÷x+3=14 | | (3m-1)-m+2=0 | | (x+27)+(2x-7)=90 | | 7x²+18x-530=0 | | 8x+21= | | F(x)=30x10 | | -4x=14=54 | | N=40(m+7) | | -5v-(-7-4v)=-2(3v-4) | | 4^4=16^x | | 2n-3=n=2 | | x/2+1=x/5+1/4​ | | 7x=x+x+x+24 | | 4=b17 | | 59-u=287 | | 6x-37=-5(2-3x) | | -2(4f-6)=36 | | (6x-1)+(5x+28)=90 | | 2(x+21)= | | x13=6 | | 4v−5=3v+4 | | (x+1)(x-7)=(x+1)(x-3) | | 11x-79=6x-47 | | 3(f+5)=18 | | 2x(x+15)=55+x | | 22=u/3+17 | | 180=15n | | 5x–3x+8=4+4x–6 | | (3x+3)/5=2x-2(x+3) | | -4(-6x+9)=5(5x-6) | | 18=b19 |

Equations solver categories